DEVELOPMENT OF EQUIPMENT MANAGEMENT SYSTEM WITH MONITORING OF WORKING CHARACTERISTICS OF TECHNOLOGICAL PROCESSES - Belousova, Maria; Aleshko, Roman; Zakieva, Rafina; Karabasheva, Malvina; Gorovoy, Sergey; Kozhemov, Sultanbek (Journal of Applied Engineering Science, 2021)
The work provides multi-purpose optimization of the baklava production process based on technology of agent systems, the intelligent environment of process control systems. The general architecture of the control system intelligent environment with agent technologies for recognizing abnormal situations was developed and adaptive baklava production regulators were synthesized. It allows you to get the specified dynamic characteristics of the control object based on the developed adaptive systems for adjusting the PID controllers, controlling the parameters of the dough, kneading, separation and baking of baklava. The proposed approach to the construction of an automated process control system with an intelligent environment will reduce the variance of fluctuations in energy consumption, increase the production rate of high-quality baklava and reduce the time for re-equipment and technological modes of operation of baklava production lines.